PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJATERHADAP KINERJA KARYAWAN PT. KERETA API INDONESIA (PERSERO) DAOP IV SEMARANG - Robin Petrus Simanjuntak; Handoyo Djoko Waluyo; Widiartanto Widiartanto (Universitas Diponegoro, 2016)
Human resources is one factor that is strategic and fundamental in the organization. The role of human resources will determine the success or failure of the organization in achieving its vision and mission that has been set. In order to determine the extent to which the presence, role and contribution of human resources in achieving organizational success, of course necessary performance measurement. Organizational culture and work discipline have influence in improving the performance of employees of PT. Kereta Api Indonesia (DAOP IV) Semarang. Good organizational culture will enhance good performance. This study aims to determine the influence of organizational culture and work discipline on employee performance. This study uses census sampling technique sampling of 58 employees of PT. Kereta Api Indonesia (DAOP IV) Semarang. Collecting data in this study using a questionnaire and interviews with technical research instruments using a questionnaire with Likert scale. The data obtained were analyzed qualitatively and quantitatively through validity and reliability test. While the test data analysis, correlation analysis, coefficient determination test, simple linear regression analysis, multiple linear regression, t-test and F test with SPSS 20.0.Statistical results known that organizational culture accounted for 22.3% and discipline accounted for 18.2% have a positive influence on employee performance. Based on the coefficient of determination in jointly influence organizational culture and work discipline against the employee's performance of 32.5%, value F count (13.233) > F table (3.16) with a significance of 0.000 < 0.05 significance level it is known that '' there is the influence of organizational culture, and work discipline on the performance of employees